Choosing again : Developing personal projects with young adults deprived of freedom - Chá, Rita Teresita (2016)
This paper develops a proposal of guidance for young people between 18 and 25 years old about to be released from the prison units of the city of La Plata. Using tools derived from the field of psychology together with strategies from other complementary disciplines, the project is aimed at providing tools that will enable these young people to outline a plan of life that will facilitate their social, personal and community re-integration. It aims to help these young people to challenge their detention conditions and can be aware of their social reality in the construction of an alternative life plan before being discharged. Our guidance plan takes into account their relational contexts to help evaluate the feasibility of projects to be developed individually, and it tries to have an impact on minimizing the inmates’ socio-criminal vulnerability. We aim at the co-construction of life strategies that break with prejudices which derive from stigmatization. The project will probably contribute to the restoration of socially positive self-esteem, to increased awareness of potentialities that the experience of confinement has debased or distorted and to the redefinition of personal, family and social histories minimizing the chances of being involved in conflict with the law again.